Novel Contribution of Secreted Amyloid-β Precursor Protein to White Matter Brain Enlargement in Autism Spectrum Disorder - Sokol, Deborah K.; Maloney, Bryan; Westmark, Cara J.; Lahiri, Debomoy K. (Frontiers in Psychiatry, 2019)
The most replicated neuroanatomical finding in autism is the tendency towards brain overgrowth, especially in younger children. Research shows that both gray and white matter are enlarged. Proposed mechanisms underlying brain enlargement include abnormal inflammatory and neurotrophic signals that lead to excessive, aberrant dendritic connectivity via disrupted pruning and cell adhesion, and enlargement of white matter due to excessive gliogenesis, and increased myelination. Amyloid-β protein precursor (APP) and its metabolites, more commonly associated with Alzheimer’s disease (AD) are dysregulated in autism plasma and brain tissue samples. This review highlights findings that demonstrate how one APP metabolite, APPα, and the ADAM family α-secretases, may lead to increased brain matter, with emphasis on increased white matter as seen in autism. APPα and the ADAM family α-secretases contribute to the anabolic, nonamyloidogenic pathway which is in contrast to the amyloid (catabolic) pathway known to contribute to Alzheimer disease. The nonamyloidogenic pathway could produce brain enlargement via genetic mechanisms affecting mRNA translation, and polygenic factors that converge on molecular pathways (mitogen-activated protein kinase/MAPK and mechanistic target of rapamycin/mTOR), promoting neuroinflammation. A novel mechanism linking the nonamyloidogenic pathway to white matter enlargement is proposed: α-secretase and/or sAPPα, activated by ERK receptor signaling activates P13K/AKt/mTOR and then Rho GTPases favoring myelination via oligodendrocyte progenitor cell stimulation (OPC) activation of cofilin. Applying known pathways in AD to autism should allow further understanding and provide options for new drug targets.